Understanding fundamentals of hepatocellular carcinoma to design next-generation chitosan nano-formulations: Beyond chemotherapy stride - Jaiswal, Neha; Chaudhari, Ravindra D.; Chaudhari, Bhushan P. (Journal of Drug Delivery Science and Technology, 2020)
Hepatocellular carcinoma (HCC) is the deadliest form of liver cancer. Clinically, the main strategies currently being used for the treatment of HCC are surgery, radiotherapy and chemotherapy. Conventional chemotherapy has major drawbacks such as poor bioavailability, high-dose requirements, adverse side effects, low therapeutic indices, and non-specific drug targeting. Therefore, targeted drug delivery systems are fast becoming new tools for the selective killing of cancer cells. Chitosan (CS) is a biodegradable, biocompatible, cationic and natural biopolymer that also exhibits anti-cancer property which is now being explored as a promising candidate for targeted drug delivery. This review outlines an overview of the causative agents, microenvironment, pathophysiology, surface-biomarkers and physiological barriers of HCC. Then, the cellular internalization pathways of nanomedicine and the important physicochemical properties of delivery agents are discussed. The benefits of targeted therapy over conventional therapy with regard to HCC are also discussed. The main objective of this review was to summarize the current knowledge in the field of chitosan-based drug delivery for the management of HCC along with its limitations in a comprehensive and systematic way. This review attempts to provide a holistic roadmap for designing the next-generation chitosan-based drug delivery systems for HCC management.
Keywords: chitosan nanoparticles; Hepatocellular carcinoma; Pathophysiology; Surface biomarkers; Targeted Drug Delivery; Tumor microenvironment